Collaboration in Development of New Drugs. Issue 11 (11th October 2021) - Tian, Zhili; Gurnani, Haresh; Xu, Yi
Abstract : The development of a new drug is costly and uncertain. As such, pharmaceutical firms often collaborate to develop new drugs. We examine the conditions under which firms should collaborate rather than compete in new drug development. We model the collaboration vs. competition decision problem for two firms using a game‐theoretic model and derive the collaboration conditions. Our study demonstrates that development cost and uncertainties in drug treatment efficacy and safety and patient enrollment drive the collaboration or competition decision for firms. We establish conditions based on probabilities of success of drug development, cost rates, and potential market shares under which the firms should collaborate, and show that there exist scenarios under which the firms actually collaborate on the lower efficacy drug. As such, firms need to take into consideration various factors such as the probability of success, the potential market share, and the development cost of each competing drug when determining whether to collaborate or compete in developing new drugs. Finally, we apply our analytical model to illustrate a case study involving collaboration between Bristol‐Myers Squibb and Pfizer. Abstract : Author Video